Hypo-osmolality activates Wnt/β-catenin mediated by AQP1 in nucleus pulposus cells degeneration: Hypo-osmolality promotes the NP cell degeneration - Zhang, Xiao; Lv, Zheng; Wei, Chengjian (Cellular and Molecular Biology, 2024)
The goals of this study were to investigate whether Wnt/β-catenin signaling plays a role in hypo-osmolality-related degeneration of nucleus pulposus (NP) cells, and if so, to define the mechanism underlying AQP1 in this effect. Human NP cells were cultured under hypo-osmotic (300/350/400 mOsm) and iso-osmotic (450 mOsm) conditions. The cell viability, AQP1, the expression of Wnt/β-catenin signaling, collagen II/I, and MMP3/9 were evaluated. To determine the effects of the Wnt/β-catenin signaling, we used the inhibitor and the activator of Wnt during the hypo-osmotic culture of NP cells. We also examined whether the silencing and overexpressing of the AQP1 gene would affect the Wnt/β-catenin expression in NP cells. Hypo-osmolality caused NP cell degeneration and activated the Wnt/β-catenin signaling but suppressed the AQP1 level. Inhibiting the Wnt/β-catenin signaling alleviated the hypo-osmolality-induced NP cell degeneration. On the contrary, activating Wnt/β-catenin aggravated the NP cell degeneration under hypo-osmotic conditions, which did not affect AQP1 expression. AQP1-overexpressed NP cells exhibited decreased Wnt/β-catenin signaling and alleviated cell degeneration under the hypo-osmotic condition. Besides, AQP1 silencing accelerated NP cell degeneration and activated Wnt/β-catenin expression compared with untreated control. Hypo-osmolality promotes NP cell degeneration via activating Wnt/β-catenin signaling, which is suppressed by AQP1 expression. The upregulation of AQP1 suppressed the Wnt/β-catenin signaling and alleviated the hypo-osmolality induced by the NP cell degeneration.